Barriers and facilitators to HPV and meningococcal vaccination among men who have sex with men: a qualitative study - Justin Naidu; Andrea N. Polonijo (BMC, 2023)
Abstract Background Men who have sex with men (MSM) have suboptimal uptake of human papillomavirus (HPV) and meningococcal vaccines. This study examines barriers and facilitators to HPV and meningococcal vaccination among MSM in a large, racially/ethnically diverse, and medically underserved U.S. region. Methods In 2020, we conducted five focus groups with MSM living in the Inland Empire, California. Participants discussed (1) their knowledge about and attitudes toward HPV, meningococcal disease, and related vaccines; and (2) factors that would encourage or discourage vaccine uptake. Data were systematically analyzed to identify salient barriers and facilitators to vaccination. Results Participants (N = 25) had a median age of 29. Most were Hispanic (68%), self-identified as gay (84%), and had college degrees (64%). Key barriers to vaccination included: (1) limited awareness and knowledge about HPV and meningococcal disease, (2) reliance on mainstream healthcare providers for vaccine information, (3) stigma and reluctance to disclose sexual orientation, (4) uncertainty about health insurance coverage and vaccine costs, and (5) distance and time required to access vaccines. Key facilitators to vaccination were: (1) vaccine confidence, (2) perceived severity of HPV and meningococcal disease, (3) bundling vaccination into routine healthcare, and (4) pharmacies as vaccination sites. Conclusions Findings highlight opportunities for HPV and meningococcal vaccine promotion, including targeted education and awareness campaigns for MSM, LGBT inclusivity training for healthcare providers, and structural interventions to improve vaccine accessibility.